Development of Economics Textbooks with a Constructivist Approach Based on the 7E Learning Cycle to Improve High School Students' Critical Thinking and Collaboration Skills - Vebrina, Dinda; Putra, Edysyah (LPPM Universitas Pendidikan Mandalika, 2024)
This research aims to develop a textbook Economics with a Constructivist Approach Based on the 7E Learning Cycle to Improve High School Students' Critical Thinking and Collaboration Skills. This research is a development research (Development Research) with the ADDIE model (Analyze, Design, Development, Implementation and Evaluation. The development of this textbook involved 4 validators who assess the format, language and content of the textbook. Data were collected using a validation sheet instrument aimed at obtaining reviews and recommendations for the developed textbook product. Validity analysis was carried out by descriptive percentage analysis by determining the Average Percentage Score (PRS) of achievement of each component of the validated aspect. Based on data analysis from the assessment results of 4 validators, the average score (PRS) of the textbook on the format aspect was 78 (moderate), language aspect 86.67 (High), and content aspect 82.22 (High), the overall average was 82.29 (High). From the PRS results obtained, it can be concluded that the economics textbook with a constructivist approach based on the Learning Cycle 7E to improve critical thinking and collaboration skills of high school students meets the validity aspect and can be implemented in high school students' economics learning.